Building Bridges: Kuwait’s Subtle Diplomacy and Humanitarian Soft Power in a Fractured Region - Lakshminarayanan, Radhika (YSU Journal of International Affairs, 2025)
Amidst the global transitions towards a multipolar order in the 21st century, the Gulf Cooperation Council (GCC) states are emerging as a crucial regional bloc aiming for wider global relevance. Among these, Kuwait, despite being a ‘small state,’ has gained respect and stature through its diplomatic acumen, playing roles as a mediator and aid giver, while committing to multilateralism. This paper examines how Kuwait’s foreign policy posture has evolved within the region’s geopolitical structure, with a primary focus on its soft power projection through subtle diplomacy. Using a historical framework, this study highlights the emergence of Kuwait as a stabilizing actor amidst growing regional rivalries through a comparative analysis. The author concludes that despite internal structural constraints and geo-strategic external pressures, Kuwait’s nuanced foreign policy approach is a good example of how small-state diplomacy can shape larger regional dynamics. Thereby, this article contributes to a broader understanding of how small states exercise global agency in regions where great power competition and intra-regional rivalries intersect.